Intramolecular Fatty Acids Distribution in the Triglycerides of Hordeum vulgare (Biological Sciences - PJSIR, 2005)
Triglycerides of a local variety of Hordeum vulgare, ‘jao-87,’ were separated from the lipids by column chromatography, purified on plain thin layer chromatography plates, and then fractionated by silver nitrate impregnated thin layer chromatography. Fatty acids composition of these fractions was verified by gas chromatography after their methylation. The distribution of fatty acids, attached at a, a’- and b-positions of the triglycerides and their fractions, was determined by lipolytic hydrolysis and subsequent gas chromatographic analysis of the 2-monoglycerides. The b-position was usually occupied by oleic, linoleic and linolenic acids, depending upon the comparative high percentage of the respective fatty acid in that triglyceride fraction.